2018
DOI: 10.2147/ppa.s180641
|View full text |Cite
|
Sign up to set email alerts
|

Current and future options for opioid use disorder: a survey assessing real-world opinion of service users on novel therapies including depot formulations of buprenorphine

Abstract: PurposeIntegrated treatment for opioid use disorder (OUD) includes opioid agonist therapy (OAT) such as methadone and buprenorphine with well-evidenced benefits. Treatment with typical existing oral medications is associated with burdens and limits to successful outcomes (frequent dosing, attendance for collection/consumption, difficulty in achieving optimal dosing, misuse, diversion, accidental exposure, and stigma from the treatment process). Novel medications include injected depot formulations with less fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 15 publications
4
50
0
1
Order By: Relevance
“…Our analyses add to a small but emergent literature on patients' views of prolonged-release buprenorphine (Gilman et al, 2018;Kenney et al, 2018). Findings support the argument that people are likely to welcome greater choice and flexibility in respect of OAT medications and delivery systems (Neale et al, 2018a(Neale et al, , 2018b.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our analyses add to a small but emergent literature on patients' views of prolonged-release buprenorphine (Gilman et al, 2018;Kenney et al, 2018). Findings support the argument that people are likely to welcome greater choice and flexibility in respect of OAT medications and delivery systems (Neale et al, 2018a(Neale et al, , 2018b.…”
Section: Discussionsupporting
confidence: 63%
“…We are not aware of any published studies on patients' experiences of receiving depot buprenorphine and limited research appears to have been conducted into their willingness to receive it. From the few studies we identified, quantitative research indicates that people who use opioids will be willing to receive depot buprenorphine (Gilman et al, 2018;Kenney et al, 2018), even though they recognize that it has both positive and negative features (Gilman et al, 2018). Qualitative research explored opioid users' views of novel opioid pharmacotherapy delivery systems, including depot injections (Neale et al, 2018a(Neale et al, , 2018b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have explored OAT client views of XR‐buprenorphine using small samples , this study builds on this previous work by undertaking an in‐depth examination of demographic and clinical correlates of these perceptions in a diverse sample of people who regularly use opioids, with varied treatment experiences. Consistent with previous studies , perceptions of XR‐buprenorphine were generally positive, with two‐thirds of the current study's sample believing it would be a good treatment option for them if it were available. Overall, less frequent contact with treatment services was viewed positively by participants (endorsed as an advantage by 76%).…”
Section: Discussionmentioning
confidence: 99%
“…To date, two studies have been conducted internationally, examining clients’ perspectives on the impacts of changes to the frequency of dosing for XR‐buprenorphine and potential safety concerns . These qualitative studies indicate that perceptions of XR‐buprenorphine injections and implants may be influenced by a range of physical, psychological and social factors .…”
Section: Introductionmentioning
confidence: 99%